MICROSTRUCTURAL CHARACTERISTIC OF N2 SHIELDING GAS IN COATING FeCrC COMPOSITE TO THE SURFACE OF AISI 1030 STEEL WITH PTA METHOD - Yildiz, T.; Gur, A. Kaya (Polish Acad Sciences Committee Metallurgy, 2011)
In this study, FeCrC powder was alloyed on the surface of AISI 1030 steel with FeCrC powder having 70% Cr ratio with the Plasma Transferred Arc Welding Method. In the coating process performed with the Plasma Transferred Arc Welding Method, N-2 gas at 1-3-5% ratio was added to the shielding gas. The coating layer was analysed using optical microscope (OM), scanning electron microscope (SEM), X-ray diffractogram (XRD) and X-ray energy dispersive spectrometer (EDS). As a result of optical microscope and microstructure analyses, it was determined that the coating layer and the sub-layer were connected to each other metallurgical and there were austenite (gamma), Fe-Cr. Fe-23(C)(6), and Cr7C3 phase and carbides and CrN in the structure.
Keywords: Plasma transferred arc coating; surface modifications; chromium carbide; chromium nitrurs; microstructure